Limitations of regional network-orientated strategies for manufacturing industries.: The case of the Neckar-Alb region in Baden-Württemberg/Germany - Grotz, Reinhold; Braun, Boris (ERDKUNDE, 1997)
Over the past decade the determinants of local and regional economic development ranked high on the research agenda in economics and economic geography alike. Despite this extensive research interest, the approaches used and the results obtained are still vague and strongly biased towards very few positive regional examples around the world. Nevertheless, the concepts derived from this work were quickly transformed into regional policy strategies. Networks and co-operations almost became key words for successful regional economic development. This paper is primarily concerned with the adoption of these concepts by regional decision-makers. The possibilities and limitations of co-operation- or network-orientated regional strategies are discussed with special reference to the Neckar-Alb region in Baden-Württemberg. This area is confronted with a severe economic downturn and massive job losses in some of its leading manufacturing sectors. Regional decision-makers try to overcome these problems with strategies which very much reflect the fashionable concepts of intensified regional co-operation and networking. In the light of our empirical findings, however, it is doubtful whether these strategies can be successful. Effective regional networks are rare highlights in the world economy. They rely on specific conditions which cannot be reproduced easily within a couple of years. Furthermore, regional actors are in a ever more weakening position to promote or control relevant factors of regional economic development in a rapidly globalising economy.